Numerical simulations of fluidized bed fast pyrolysis of biomass through computational fluid dynamics - Sia, Sheng Qiang; Wang, Wei-Cheng (Renewable energy, 2020)
In this study, computational fluid dynamics (CFD) was applied for simulating the hydrodynamics and chemical kinetics for the fluidized bed biomass fast pyrolysis. Based on the Euler-Euler multiphase framework, standard K-ε model and Finite-Rate/Eddy-Dissipation model were selected for the viscous and the species transport model, respectively. Syamlal O’brien model and Arrhenius kinetic model were chosen as the drag and reaction kinetics model, respectively. The volume fractions as well as the temperature distributions of the fluidizing gas, biomass and fluidizing sand at the fluidization velocity of 0.6 m/s were numerically observed. The simulation of the reaction temperature influence on product yield agreed well with the lab-scale experimental results. The distributions of the gas products show that CO and H2 are mostly at the lower part of the reactor, CH4 is in the freeboard region and CO2 is at both the reaction and freeboard zone. The proposed CFD model was expected to make contributions for improving the internal process and reactor optimization for biomass fluidized bed fast pyrolysis. •The hydrodynamics and chemical kinetics for fluidized bed pyrolysis was simulated.•The transitions of fluidization for gas, biomass and sand were numerically observed.•The simulated results well-agreed with the experimental ones for product yields.•The distributions of CO, H2, CH4 and CO2 in the reactor were also exhibited.